IPTEK NASIONAL UNTUK PERCEPATAN TANGGUNG JAWAB SOSIAL SWASTA - Dicky Rezady Munaf (Jurnal Sosioteknologi, 2007)
The needs of citizens include education, health, transportation, and employment for their living. To meet the needs, the participation of privates is very important. The privates' care for the society is the implementation of social responsibility to improve sustainable production development, stabilization of related production structure, and the development of sustainable innovation conditions. Social responsibility of privates must be related to the main competency of the corporation, and at the same time will give an impact to the wealth of neighboring community.